Enhancing Learning Outcomes: A Study of Key Educational Method Drivers - Syafruddin Rais; Toni Ari Wibowo (Jurnal Penelitian Pendidikan IPA, 2025)
The effectiveness of learning methods continues to face numerous challenges, particularly in the rapidly evolving digital era. This study aims to analyze the factors influencing the effectiveness of learning methods within the context of higher education. A quantitative approach was employed through a survey, with data collected using questionnaires distributed to 114 students from the Culinary Management Department. The data were analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method with SmartPLS version 4.0 software. The prerequisite analysis confirmed that the measurement model met the criteria for validity and reliability. The research findings indicate that student characteristics have a positive but statistically insignificant influence on the effectiveness of learning methods, although the small effect size still holds some relevance. Similarly, the quality of learning exhibits a positive yet non-significant relationship with learning effectiveness, with a relatively greater effect size than student characteristics. Conversely, the learning environment shows a negative and negligible correlation with learning effectiveness, marked by a very minimal effect size. In contrast, learning technology emerges as a key factor, showing a significant and positive impact on the effectiveness of learning methods, supported by a relatively substantial effect size. In conclusion, learning technology plays a critical role in enhancing the effectiveness of learning in the digital era, while other factors may require reevaluation or strategic integration to better support educational outcomes.